Evaluasi Keberhasilan Gerakan Indonesia Sadar Pajak Tahun 2018 - Septian Bayu Kristanto; Vira Anggaraeni (Universitas Trunojoyo Madura, 2019)
Tax revenues accounted for more than 80% and therefore, a high level of public awareness of taxes was needed. So the Directorate General of Taxes made various efforts to increase public awareness of taxes and one of them was the Tax Awareness Indonesia Movement program. The research entitled